Cerebral Aspergilloma in Patient with Diabetes – A Case Report with Short Literature Review - Ivanova, Koni; Valkanov, Stefan; Petrov, Bozhidar; Mindov, Ivan; Gulubova, Maya (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: In the recent years, the incidence of fungal brain abscess has been rising as a result of the increased use of corticosteroid therapy, broad-spectrum antimicrobial therapy, and immunosuppressive agents. Aspergillosis of the central nervous system (CNS) is reported in 10%–20% of the patients having invasive fungal disease. Commonly, the disease is observed in immunocompromised or immunosuppressed patients; also, patients who suffered traumatic head injury are reported as well to develop the infection due to due cranial defect accompanied by dural tearing. Symptoms are non-specific neurologic manifestations. CASE PRESENTATION: We presented a case of a 68-year-old man who had diabetes mellitus type II. He was admitted to in neurosurgery clinic due reported head trauma. Initially, he complained of a headache, dizziness, slurred speech, nausea, and pain in the right ear with tinnitus and pain in his right upper teeth – continuous for a month. The patient was conscious, adequate, Glasgow Coma Scale – 15 points, with left-sided hemiparesis, general symptomatic syndrome. An emergent computed tomography scan was performed, which showed tumorous formation in patient’s right temporal lobe that had mass effect and compression of the right lateral ventricle. The patient was discussed on a emergent clinical counsel and it was decided that he was shown for surgical treatment. An informed consent was signed by the patient and his relatives. After the surgery intervention – the histological result of the biopsy was aspergilloma of the brain and the microbiological result was Aspergillus fumigatus. CONCLUSION: The prognosis for CNS aspergillosis is poor, but the early diagnosis and effective medical and surgical treatments may reduce morbidity and mortality.